Nonlinear (2+1)-dimensional systems solvable through asymptotic modules - Jaulent, Marcel; Manna, Miguel A. [UNESP]; Martinez Alonso, Luis (Elsevier, 1989)
Some nonlinear differential systems in (2+1) dimensions are characterized by means of asymptotic modules involving two poles and a ring of linear differential operators with scalar coefficients.Rational and soliton-like are exhibited. If these coefficients are rational functions, the formalism leads to nonlinear evolution equations with constraints. © 1989.